2020
DOI: 10.26480/wcm.02.2021.53.57
|View full text |Cite
|
Sign up to set email alerts
|

Role of Phycoremediation in Domestic Wastewater Treatment

Abstract: Conventional domestic wastewater treatment in most developing countries is confined to secondary treatments, mainly focusing on solids and organics removal, which results in eutrophication when the effluents are discharged into receiving bodies. Thus, to resolve the issues associated with the conventional treatment system, in the present study, microalgae was introduced in the primary treated effluent collected from a sewage treatment plant to study the efficiency of the system in reducing eutrophication and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The concentration of TDS, TS, and TSS of untreated DWW was 975.48, 1685.36, and 709.88 mg/ l respectively and they were reduced to 832, 1446.37, and 614.37 mg/l (Table 2). Moondra et al (2021b) reported that TDS, TS, and TSS were effectively removed by C. vulgaris. The maximum removal of 14.71% (TDS) was achieved while a minimum removal efficiency of TSS (13.45%) and 14.18% (TS) was recorded with C. vulgaris treatment.…”
Section: Properties Of Raw Domestic Wastewatermentioning
confidence: 99%
“…The concentration of TDS, TS, and TSS of untreated DWW was 975.48, 1685.36, and 709.88 mg/ l respectively and they were reduced to 832, 1446.37, and 614.37 mg/l (Table 2). Moondra et al (2021b) reported that TDS, TS, and TSS were effectively removed by C. vulgaris. The maximum removal of 14.71% (TDS) was achieved while a minimum removal efficiency of TSS (13.45%) and 14.18% (TS) was recorded with C. vulgaris treatment.…”
Section: Properties Of Raw Domestic Wastewatermentioning
confidence: 99%
“…One effect on the physiology of the algae cells was the change in pH, which had an effect on one form of nutrient through an increase in alkalinity [66] after photosynthesis due to an increase in the pH of the effluent [67]. Increasing the pH causes self-flocculation, which eliminates algae suspended in the effluent and reduces the phosphorus concentration thanks to the interaction between cations and phosphates, which precipitate in a complex algae-mineral structure [68].…”
Section: Removal Of Ammoniamentioning
confidence: 99%